On the Global Character of the Rational System $\boldsymbol{\displaystyle{ x_{n+1}=\frac{α_1 }{A_1+ B_1 x_n + y_{n}} \quad AND \quad y_{n+1}=\frac{α_2+β_2 x_n}{A_2+B_2 x_n+C_2 y_n}}}$ - Drymonis, E.; Ladas, G. (Sarajevo Journal of Mathematics, 2024)
In this paper we investigate the global stability character of the rational system in the title with the parameters $B_1, B_2, A_2+C_2$ positive, the parameters $A_1,α_2,β_2, A_2, C_2$ nonnegative, and with arbitrary nonnegative initial conditions such that the denominators are always positive. 2000 Mathematics Subject Classification. 39A10